PENGARUH MODEL PICTURE AND PICTURE TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI DI SEKOLAH DASAR - Novita, Maya; Halidjah, Siti; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this research is "How is the effect of the implementation of a picture and picture models on the narrative essay writing skills of 3rd grade students of elementary school number 37 Pontianak Tenggara?â€. This study aims to analyze the effect of the implementation of a picture and picture models on the narrative essay writing skills of 3rd grade students of elementary school number 37 Pontianak Tenggara. This research uses experimental method, with Quasi Experimental Design form. Population and sample in this research is all 3rd grade students of elementary school number 37 Pontianak Tenggara which amounts to 66 people. Techniques used in data collection is a measurement technique with the tool used is essay-shaped written test and documentary/ bibliography study technique that is collecting photographs of research conducted. Based on the data analysis obtained the average of the result of the final test (post-test) of the experimental class is 81,15 and the means of the final test result (post-test) of control class student is 73,04. After the t-test obtained of 3,1662 while () = 5% of 1,6701, it turns Â â‰¥ Â or 3,1662 â‰¥ 1,6701 which means there is a significant influence on the application of the picture and picture model. From the calculation of the effect size obtained by 0.87 with the criteria classified as high. This means that the application of picture and picture models has a high influence on the narrative essay writing skills of 3rd grade students of elementary school number 37 Pontianak Tenggara.Â Keyword: Influence, Picture and Picture Models, Narrative EssayÂ